Acoustic repertory of Hypsiboas exastis (Caramaschi and Rodgrigues, 2003) (Amphibia, Hylidae). - Loebmann, Daniel; Zina, Juliana; dos Santos Araujo, Olivia Gabriela; Toledo, Luis Felipe; Baptistia Haddad, Celio Fernando (My University, 2008)
Advertisement, territorial, and distress calls of Hypsiboas exastis, a species of the Hypsiboas faker group, are described for the first time. Acoustic records were obtained of one specimen found at the Municipality of Urucuca, state of Bahia, Brazilian eastern cost. We compared the advertisement calls of H. exastis with those of H. lundii and H. pardalis (the closest related species) and suggested a closer similarity with H. lundii.